The Influence of Curriculum, Accounting Expertise and Lecturer Competence on Student Work Readiness in the VUCA Era - Susanti, Christina (Indonesian Journal of Business Analytics, 2024)
The occurrence of a phenomenon of rapid change in all industries due to the VUCA era and its impact on the demand for workforce work readiness in the hotel industry is the background for this research. This study aims to analyze the work readiness of students at the Hospitality Accounting Management Study Program (Prodi MAH) at the Politeknik Pariwisata Bali based on the influence of curriculum factors, accounting expertise and lecturer competence. This research is quantitative research where data collection is carried out by distributing online questionnaires using Google Forms to all students of the Prodi MAH. Sampling using a census consists of Prodi MAH 8th semester students, as many as 60 people. Furthermore, the data was processed with SEM PLS using smartPLS software version 4.0. The findings indicated that curriculum and accounting expertise positively, significantly and directly impacted work readiness and indirectly affected work readiness through the mediation of lecturer competence.